IMPROVING STUDENTS’ CREATIVE THINKING ABILITY AND LEARNING OUTCOMES THROUGH THE IMPLEMENTATION OF PROBLEM BASED LEARNING MODEL AT ELEMENTARY SCHOOLS - Yunita Cahyarini; Maria Melani Ika Susanti; Maria Indarti Rustamti (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2021)
This classroom action research aimed to improve creative thinking skills and social studies learning outcomes by implementing problem-based learning model. This research was motivated by the low creative thinking and learning outcomes of the fifth grade elementary school students. Data on creative thinking and learning outcomes in this Classroom Action Research were collected through interviews, observations, and questionnaires. The subjects of this study were 46 students of grade V. This research was carried out in two cycles with the research procedures consisting of planning, implementation, observation, and reflection. The results showed that problem-based learning model improved the students’ creative thinking and learning outcomes for social studies material at grade V elementary school. This was showed in the increase of the creative thinking variable with an average initial condition value of 36.83 (creative enough), the first cycle of 43.04 (creative enough) and the second cycle of 45.07 (creative). The variable of students’ learning outcomes in the initial data showed an average value of 68.09, the first cycle was 70.33, and the second cycle was 78.59.